Intragenic epigenetic changes modulate NCAM alternative splicing in neuronal differentiation - Schor, Ignacio Esteban (2013)
Alternative splicing contributes to cell type-specific transcriptomes. Here, we show that changes in intragenic chromatin marks affect NCAM (neural cell adhesion molecule) exon 18 (E18) alternative splicing during neuronal differentiation. An increase in the repressive marks H3K9me2 and H3K27me3 along the gene body correlated with inhibition of polymerase II elongation in the E18 region, but without significantly affecting total mRNA levels. Treatment with the general DNA methylation inhibitor 5-azacytidine and BIX 01294, a specific inhibitor of H3K9 dimethylation, inhibited the differentiation-induced E18 inclusion, pointing to a role for repressive marks in sustaining NCAM splicing patterns typical of mature neurons. We demonstrate that intragenic deployment of repressive chromatin marks, induced by intronic small interfering RNAs targeting NCAM intron 18, promotes E18 inclusion in undifferentiated N2a cells, confirming the chromatin changes observed upon differentiation to be sufficient to induce alternative splicing. Combined with previous evidence that neuronal depolarization causes H3K9 acetylation and subsequent E18 skipping, our results show how two alternative epigenetic marks regulate NCAM alternative splicing and E18 levels in different cellular contexts.